Guillaume Faye's legacy: the alt-right and Generation Identity. Issue 1 (2nd January 2023) - Maly, Ico
ABSTRACT: The alt-right, the different chapters of the pan-European movement Generation Identity and the rise of the so-called radical right populist parties in the West have been responsible for the renewed interest in the metapolitical project of La Nouvelle Droite . In this attention, we see a strong focus on the ideological impact of this school of thought and on Alain de Benoist in particular. This article adds new insights into the 21 st century legacy of La Nouvelle Droite by focusing on the uptake and reproduction of the work of GRECE's so-called number two Guillaume Faye. Whereas Alain de Benoist is usually seen as the transnational messenger of La Nouvelle Droite, Guillaume Faye has gained far less attention. The article presents a digital ethnographic discourse analysis of Faye's work and his uptake by new right and identitarian activists around the world. It makes two arguments. The first one is empirical, namely that Faye's legacy should be assessed in the context of the contemporary rise of new right activism and identitarianism in particular. The second argument is theoretical and stresses the importance of analysing the role of (digital) media in the distribution of ideas and ideologies.